The aesthetics of Burke's constitutionalism: A dialectical reading. (January 2021) - Rustighi, Lorenzo
I propose taking the beautiful and the sublime in Edmund Burke not just as aesthetic but also as theoretical categories which can help us read his constitutional thought in dialectical terms. I suggest indeed that his usage of these categories in the Reflections on the Revolution in France points to a consistently held argument concerning the aporias of early-modern contractarian theories and their influence on the French Revolution. My hypothesis is that for Burke the Revolution is unable to think of any concrete relation between beauty and sublimity, insofar as they can be associated, respectively, with particularity and universality. Furthermore, I underscore how Burke's defence of partial representation against contractarian representation aims to overcome this impasse. My goal is to demonstrate that Burke raises decisive questions as to the intrinsically anti-democratic effects of the contractarian concept of democracy and is still useful to confront the contemporary crisis of democratic participation.